FACTORS ASSOCIATED WITH NURSE PERFORMANCE AT THE INPATIENT INSTALLATION OF THE SOUTH TANGERANG CITY GENERAL HOSPITAL IN 2023 - Sahira Ristania Jahra; Noor Latifah; Fini Fajrini; Hardiman SG (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
The primary focus of health services is nurse performance since maintaining and enhancing the quality of health services requires assessment. A bridge to guaranteeing the caliber of services rendered to patients is good performance. The fact that performance statistics did not rise by 50% between 2013 and 2015—the target performance criterion is 70–80%—indicates that performance levels among Indonesian nurses are still very poor and have not significantly improved. Data on nurse performance at RSU Kota Tangerang Selatan for the years 2019 (82%), 2020 (85.4%), 2021 (74.3%), and 2022 (75.8%). It is well known that in 2021–2022, nurses' performance did not meet the 80% target. Finding the variables associated with nurses' performance at the South Tangerang City Public Hospital's inpatient installation in 2023 was the aim of this study. This study's methodology combined a cross-sectional study design with a quantitative approach. With 59 respondents overall, complete sampling was the sample strategy employed in this investigation. The data was analyzed using the chi-square test and SPSS software. Age, gender, education, and years of service did not correlate with nursing performance, according to the bivariate analysis (p-value 0.503; 0.481; 0.219; 0.814 > 0.05). However, there was a correlation between nurse performance and the work environment (p-value 0.000 < 0.05) and work discipline (p-value 0.008 <0.05).